2019
DOI: 10.1093/jas/skz166
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lipopolysaccharide-induced immune stimulation and maternal fish oil and microalgae supplementation during late pregnancy on nursery pig hypothalamic–pituitary–adrenal function1

Abstract: The present study used Escherichia coli lipopolysaccharide (LPS) to investigate whether maternal immune challenge during late gestation altered programming of the offspring hypothalamus and hypothalamic–pituitary–adrenal axis (HPAA). In addition, interactions of maternal diet, supplementation with fish oil (FO) or microalgae (AL), and complex vs. simple weaning diets were investigated. Briefly, Landrace × Yorkshire sows (N = 48) were randomly assigned to diets supplemented with FO, AL, or a standard gestation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…In addition, maternal FO diets appeared to alleviate LPS-induced decreased weight gain of piglets and colostrum production, although these effects were not statistically significant, suggesting that feeding FO to sows as a source of n-3 PUFA may play an important role in regulating prenatal maternal stress. Similarly, a recent study demonstrated that maternal n-3 PUFA dietary supplementation attenuated the sow fever response to inflammatory stress challenges [14].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, maternal FO diets appeared to alleviate LPS-induced decreased weight gain of piglets and colostrum production, although these effects were not statistically significant, suggesting that feeding FO to sows as a source of n-3 PUFA may play an important role in regulating prenatal maternal stress. Similarly, a recent study demonstrated that maternal n-3 PUFA dietary supplementation attenuated the sow fever response to inflammatory stress challenges [14].…”
Section: Discussionmentioning
confidence: 90%
“…A total of sixty multiparous sows (Landrace × Yorkshire; 3 to 5 of parity) were randomly selected and assigned into three dietary treatment groups (3% SO, 3% CO and 3% FO) based on backfat thickness and body weight (n = 20 per group) using a randomized complete block design. The dose of 3% was included as previously described, which showed beneficial effects of FO on the hypothalamic-pituitary-adrenal function in sows and offspring [14]. All sows in the present experiment were artificially inseminated by pooled semen from three Duroc boars .…”
Section: Animals Diets and Experimental Designmentioning
confidence: 99%
“…This study is the first to investigate the effects of maternal AL and FO supplementation in combination with maternal LPS challenge in late gestation on adrenal mRNA expression in swine. The animals in this study were previously used to the assess acute-phase response to an LPS challenge ( You et al., 2019 ). The results from this study showed differential effects of maternal gestation dietary treatment and maternal LPS status, leading to the hypothesis that the maternal treatments would also influence the adrenal transcriptome of the offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Following the LPS challenge, adrenal tissue was selected from 24 of the male offspring ( n ​= ​4/maternal gestation dietary treatment and maternal LPS status). The adrenal gland was selected for microarray analysis due to previously observed differences in the offspring cortisol response following LPS challenge ( You et al., 2019 ). Total RNA was extracted from 20-30 ​mg of adrenal tissue using the Qiagen RNeasy extraction kit (Qiagen, Valencia, CA, USA) as per the manufacturer’s specifications.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation